Efficient co-conversion process of chicken manure into protein feed and organic fertilizer by Hermetia illucens L. (Diptera: Stratiomyidae) larvae and functional bacteria. (1st July 2018) - Xiao, Xiaopeng; Mazza, Lorenzo; Yu, Yongqiang; Cai, Minmin; Zheng, Longyu; Tomberlin, Jeffery K.; Yu, Jeffrey; van Huis, Arnold; Yu, Ziniu; Fasulo, Salvatore; Zhang, Jibin
Abstract: A chicken manure management process was carried out through co-conversion of Hermetia illucens L. larvae (BSFL) with functional bacteria for producing larvae as feed stuff and organic fertilizer. Thirteen days co-conversion of 1000 kg of chicken manure inoculated with one million 6-day-old BSFL and 10 9  CFU Bacillus subtilis BSF-CL produced aging larvae, followed by eleven days of aerobic fermentation inoculated with the decomposing agent to maturity. 93.2 kg of fresh larvae were harvested from the B. subtilis BSF-CL-inoculated group, while the control group only harvested 80.4 kg of fresh larvae. Chicken manure reduction rate of the B. subtilis BSF-CL-inoculated group was 40.5%, while chicken manure reduction rate of the control group was 35.8%. The weight of BSFL increased by 15.9%, BSFL conversion rate increased by 12.7%, and chicken manure reduction rate increased by 13.4% compared to the control (no B. subtilis BSF-CL). The residue inoculated with decomposing agent had higher maturity (germination index >92%), compared with the no decomposing agent group (germination index ∼86%). The activity patterns of different enzymes further indicated that its production was more mature and stable than that of the no decomposing agent group. Physical and chemical production parameters showed that the residue inoculated with the decomposing agent was more suitable for organic fertilizer than the no decomposing agent group. Both, the co-conversion of chicken manure by BSFL with its synergistic bacteria and the aerobic fermentation with the decomposing agent required only 24 days. The results demonstrate that co-conversion process could shorten the processing time of chicken manure compared to traditional compost process. Gut bacteria could enhance manure conversion and manure reduction. We established efficient manure co-conversion process by black soldier fly and bacteria and harvest high value-added larvae mass and biofertilizer. Highlights: Established efficient manure co-conversion process by black soldier fly and bacteria. Gut bacteria could enhance manure conversion and manure reduction. Co-conversion process could shorten the processing time of chicken manure. Co-conversion could harvest high value-added larvae mass and biofertilizer.